👤

(2׳-3ײ+5×-1)+(3׳-3ײ-2×+4)=5׳+6ײ+3×+3​

Sagot :

Answer:

x=0

Step-by-step explanation:

Let's solve your equation step-by-step.

2x3−3x2+5x−1+3x3−3x2−2x+4=5x3+6x2+3x+3

5x3−6x2+3x+3=5x3+6x2+3x+3

Step 1: Subtract 5x^3 from both sides.

5x3−6x2+3x+3−5x3=5x3+6x2+3x+3−5x3

−6x2+3x+3=6x2+3x+3

Step 2: Subtract 6x^2 from both sides.

−6x2+3x+3−6x2=6x2+3x+3−6x2

−12x2+3x+3=3x+3

Step 3: Subtract 3x from both sides.

−12x2+3x+3−3x=3x+3−3x

−12x2+3=3

Step 4: Subtract 3 from both sides.

−12x2+3−3=3−3

−12x2=0

Step 5: Divide both sides by -12.

−12x2

−12

=

0

−12

x2=0

Step 6: Take square root.

x=±√0

x=0

Answer:

x=0

pabrainliest